Revisiting PNS Plasticity: How Uninjured Sensory Afferents Promote Neuropathic Pain - Tran, Emily L.; Crawford, LaTasha K. (Frontiers in Cellular Neuroscience, 2020)
Despite the widespread study of how injured nerves contribute to chronic pain, there are still major gaps in our understanding of pain mechanisms. This is particularly true of pain resulting from nerve injury, or neuropathic pain, wherein tactile or thermal stimuli cause painful responses that are particularly difficult to treat with existing therapies. Curiously, this stimulus-driven pain relies upon intact, uninjured sensory neurons that transmit the signals that are ultimately sensed as painful. Studies that interrogate uninjured neurons in search of cell-specific mechanisms have shown that nerve injury alters intact, uninjured neurons resulting in activity that drives stimulus-evoked pain. This review of neuropathic pain mechanisms summarizes cell-type specific pathology of uninjured sensory neurons and the sensory ganglia that house their cell bodies. Uninjured neurons have demonstrated a wide range of molecular and neurophysiologic changes, many of which are distinct from those detected in injured neurons. These intriguing findings include expression of pain-associated molecules, neurophysiological changes that underlie increased excitability, and evidence that intercellular signaling within sensory ganglia alters uninjured neurons. In addition to well-supported findings, this review also discusses potential mechanisms that remain poorly understood in the context of nerve injury. This review highlights key questions that will advance our understanding of the plasticity of sensory neuron subpopulations and explore a role for uninjured neurons in developing anti-pain therapies.